Development Strategy for Hybrid Corn Farming on Dryland Areas in Labangka, Sumbawa Regency - Azhari, Rizka; Sjah, Taslim; Hayati, Hayati (Jurnal Biologi Tropis, 2026)
Labangka District in Sumbawa Regency is a central area for hybrid maize production in West Nusa Tenggara Province; however, dryland hybrid maize farming in this region currently faces several challenges. This study aims to: (1) identify the internal and external factors affecting hybrid maize farming, and (2) formulate a development strategy for dryland hybrid maize farming in Labangka, Sumbawa Regency. A descriptive research method was employed, and data were collected through a survey utilizing interviews with 30 respondents selected via purposive sampling, consisting of 15 respondents from Suka Mulia Village and 15 from Suka Damai Village. The collected data were analyzed using SWOT analysis. The results indicate that the primary strategy for developing dryland hybrid maize farming in Labangka, Sumbawa Regency, is the WO (Weakness–Opportunities) strategy, which minimizes existing weaknesses to capture marketing opportunities. This strategy includes: (1) adopting digital technology and weather information systems to overcome information limitations and rainfall dependence, (2) participating in government-supported technical training for cultivation and integrated pest management, and (3) utilizing the People's Business Credit (KUR) scheme or government capital assistance to strengthen farmers' financial capacity.